THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF OPTIMIZATION OF THE TRAINING PROCESS AND STRATEGIES FOR TRAINING STUDENT-ATHLETES OF HIGH QUALIFICATION IN TEAM SPORTS - Vozhzhov, Illia; Maievskyi, Mykola; Masliuk, Ruslan; Ilchenko, Serhii; Penzai, Sergii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article discloses the main theoretical and methodological foundations of optimization of the training process and strategies for training student-athletes of high qualification in team sports. Team sports are particularly popular in Olympic and professional sports. The modern system of sports training is characterized by progressive principles, a wide range of interdependent tasks, scientifically based selection of means and methods, promising long-term planning, high organization of control, provision of hygienic conditions, etc. The purpose is to substantiate and experimentally test the theoretical and methodological foundations of optimizing the training process and the strategy of training student-athletes of high qualification in team sports on the basis of theoretical and practical analysis of the problem under study; to develop the content of the training process of student-athletes of high qualification in team sports. To achieve the goals, the following methods are used: verbal, visual and practical. These methods are most often used to optimize the training process and training strategy for highly qualified student-athletes in team sports. Also, we describe the methods of optimizing the training process and strategies for training student-athletes of high qualification in team sports, which are divided into general pedagogical, specific, additional methods that are specially developed for the needs of sports practice and optimization of the training process. The content of the training process of student-athletes of high qualification in game sports has been developed, which allows purposeful planning and adjustment of tactics and strategy of training student-athletes in team sports on an objective basis, can be used in higher educational institutions that train student-athletes, and can also be concluded in textbooks and methodological recommendations.